Financial Distress and Earnings Management: The Role of Internal Control as Moderating Variable - Feni Wilamsari; Siti Maria Wardayati; Agus Wahyu Winarno (International Journal of Social Science and Business, 2022)
Various types of potential risks, such as the COVID-19 pandemic we are currently facing, will ultimately affect the success of business performance. Therefore, in an effort to cover up these problems, managers sometimes make various efforts to maintain corporate image, one of which is earnings management. Earnings management actions are often seen as opportunistic behavior that harms many parties, especially investors. Using a sample of manufacturing companies listed on the Indonesian Stock Exchange for the period 2017-2019, this study investigates the effect of financial distress on earnings management behavior and further investigates the role of internal control as moderation. The results show that companies under higher financial distress pressure tend to have managers practice earnings management to cover up poor performance. In addition, the leverage control variable has an influence on earnings management. Internal control able to moderate the relationship between financial distress and earnings management. This study provides additional information on earnings management and the role of internal control for companies with financial distress. Furthermore, this research also has implications for regulators regarding the importance of internal control standards for companies.